Rapid Development of Achalasia After SARS-CoV-2 Infection: Polymerase Chain Reaction Analysis of Esophageal Muscle Tissue - Samo, Salih; Hamo, Falak; Hamza, Ameer; Yadlapati, Rena; Kahrilas, Peter J.; Wozniak, Ann (The American journal of gastroenterology, 2024)
INTRODUCTION:Achalasia has been linked to viruses. We have observed cases of rapid-developing achalasia post-coronavirus disease 2019 (COVID-19).METHODS:We aimed to prospectively evaluate esophageal muscle for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) from patients with rapid-onset achalasia post-COVID-19 and compare them with achalasia predating COVID-19 and achalasia with no COVID-19.RESULTS:Compared with long-standing achalasia predating COVID-19 and long-standing achalasia with no COVID-19, the subjects with achalasia post-COVID-19 had significantly higher levels of messenger RNA for the SARS-CoV-2 nucleocapsid (N) protein, which correlated with a significant increase in the inflammatory markers NOD-like receptor family pyrin domain-containing 3 and tumor necrosis factor.DISCUSSION:SARS-CoV-2, the virus responsible for COVID-19, is a possible trigger for achalasia.